Penerapan Ketentuan Pemutusan Hubungan Kerja Terhadap Karywan Pada Perusahaan Yang Dinyatakan Pailit - Yudhi Priyo Amboro; Jemmy Edi (Journal of Judicial Review, 2014)
Inequality position between workers and employers have recognized the government passed Law No. 13 of 2003 on Labor on March 25, 2003. Under this law has regulated in detail the rights and obligations between employers and workers. The fact that the activities of employers do not always benefit resulting company established to carry out certain business went bankrupt. State of the bankrupt company that can not meet all of its obligations to its creditors could cause the company submitted that bankrupted. The inequality of the employers and workers are more Likely to occur when the company Suffered loss when running the business processes. Even before the company filed for bankruptcy, the workers have experienced the uncertainty of payment rights.Methodology used in this research is normative juridical law-based comparative law. The data used in this research is secondary data obtained from the literature (library research). Once all the data is collected, then processed and analyzed to find legal issues become the object of study and conclude, then described descriptively.The results showed that the unequal position between the employer and the worker actually happening in companies that declared bankruptcy that the Limited Liability Metro Batavia, Harimas Jaya Plywood Company Limited, and Limited Liability Company Sindoro Cleft Wood Industry.